Actual 10‐year survivors following resection of adrenocortical carcinoma. Issue 8 (16th September 2016) - Tran, Thuy B.; Postlewait, Lauren M.; Maithel, Shishir K.; Prescott, Jason D.; Wang, Tracy S.; Glenn, Jason; Phay, John E.; Keplinger, Kara; Fields, Ryan C.; Jin, Linda X.; Weber, Sharon M.; Salem, Ahmed; et al.
Abstract : Background: Adrenocortical carcinoma (ACC) is a rare and aggressive malignancy with limited therapeutic options beyond surgical resection. The characteristics of actual long‐term survivors following surgical resection for ACC have not been previously reported. Method: Patients who underwent resection for ACC at one of 13 academic institutions participating in the US Adrenocortical Carcinoma Group from 1993 to 2014 were analyzed. Patients were stratified into four groups: early mortality (died within 2 years), late mortality (died within 2–5 years), actual 5‐year survivor (survived at least 5 years), and actual 10‐year survivor (survived at least 10 years). Patients with less than 5 years of follow‐up were excluded. Results: Among the 180 patients available for analysis, there were 49 actual 5‐year survivors (27%) and 12 actual 10‐year survivors (7%). Patients who experienced early mortality had higher rates of cortisol‐secreting tumors, nodal metastasis, synchronous distant metastasis, and R1 or R2 resections (all P < 0.05). The need for multi‐visceral resection, perioperative blood transfusion, and adjuvant therapy correlated with early mortality. However, nodal involvement, distant metastasis, and R1 resection did not preclude patients from becoming actual 10‐year survivors. Ten of twelve actual 10‐year survivors were women, and of the seven 10‐year survivors who experienced disease recurrence, five had undergone repeat surgery to resect the recurrence. Conclusion: Surgery for ACC can offer a 1 in 4 chance of actual 5‐year survival and a 1 in 15 chance of actual 10‐year survival. Long‐term survival was often achieved with repeat resection for local or distant recurrence, further underscoring the important role of surgery in managing patients with ACC. J. Surg. Oncol. 2016;114:971–976 . © 2016 Wiley Periodicals, Inc.